Teeth infection may shunt through Fontan in high-altitude conditions. (2018)
The Fontan surgery involves the creation a conduit between the inferior vena cava and the right pulmonary artery. This conduit has a small fenestration that shunts the blood from right to left in case the pulmonary blood flow is limited; namely, if the pulmonary vascular resistance (PVR) is increased then the shunt is increased. Bacteria may bypass the pulmonary circulation and easily get access to the systemic circulation (bacteremia). We report the case of a patient that underwent Fontan surgery in 2010 and remained in a high-altitude city for 7 years, during this time he was asymptomatic until 2017 when he developed a brain abscess due to Streptococcus gordonii, a pathogen of dental plaque. Since high-altitude may raise PVR in response to reduction in the partial pressure of oxygen, we conclude that the long-term outcome of increased altitude on Fontan hemodynamics can lead to the shunt of teeth flora and consequently leading to severe infections.